Photovoltaic System: Case Studies - Durusu, Ali; Nakir, Ismail; Tanrioven, Mugdesem (SPRINGER INTERNATIONAL PUBLISHING AG, 2017)
Solar energy is one of the most important energy, which is environmentally friendly such as clean, inexhaustible and free, among the renewable energy sources. Studies on solar photovoltaic (PV) energy generation system were promoted in last two decades. The main application of PV systems are in stand-alone (water pumping, lighting, electrical vehicle, etc.), hybrid and grid-connected (PV power plants) configuration. Stand-alone PV power generation system is considered as good alternative for places that are far from conventional power generation/transmission/distribution system. PV generation systems have two big problems; PV conversion efficiency is very low and PV electricity generation is effected from changing of weather condition. PV output varies periodically in a year and in a day, and is not stable due to environmental condition. Accordingly, in order to increase PV output and PV efficiency, it is crucial to analyze PV output considering solar radiation, temperature, wind speed, shadow, etc. Maximum power point trackers (MPPTs) are employed for extracting power from photovoltaic (PV) panels. MPPTs enforce the solar modules to operate at maximum power point (MPP) under the fluctuations of ambient conditions. Therefore, they take a vital role for increasing of PV system efficiency. In this part, the case studies of MPPT system, which includes stand-alone and hybrid PV systems, will be briefly reviewed, followed by discussion of the MPPT modeling, design, etc. Several stand-alone and hybrid MPPT application will be presented. Latest developments in MPPT methods will be summarized. Finally some of the present challenges facing the MPPT techniques will be explored.
Keywords: Photovoltaic systems; Case studies; MPPT algorithms; MPPT algorithm modeling; POINT TRACKING TECHNIQUES; POWER; ALGORITHMS; MPPT; Energy & Fuels